Heterogeneous distributed parallel programming for coordination in software development - Chia-Chu Chiang (19th International Conference on Advanced Information Networking and Applications (AINA'05) Volume 1 (AINA papers), 2005)
We are presenting a formal specification-based approach to heterogeneous distributed parallel programming. A specification language is used to describe system behaviors. The specification is then analyzed to create a multiparty interaction interface description describing the properties of the multiparty interactions among processes. Our language mapping approach allows a multiparty interaction interface description automatically created in any target programming language. Developers can then write a program in the target language to include the description for execution. A familiar programming model is provided to support implicit communication, concurrency, synchronization, and parallelism in systems through an implicit coordination-oriented approach. In other words, developers do not have to explicitly express communication, concurrency, synchronization, and parallelism when they are developing heterogeneous distributed and parallel systems.